Improving source-sink relationship and harvest index through assimilate partitioning in sunflower (Helianthus annuus L.) - Thimmappa, K N; Kothathi, S S (Plant Science Today, 2026)
Sunflower (Helianthus annuus L.) production in India is constrained by its cultivation on marginal, nutrient- and moisture-deficient lands. This study aimed to enhance sunflower productivity by improving assimilate partitioning efficiency and source-sink relationships. This shows common limitations of low harvest index (HI) and inefficient nutrient allocation in the sunflower crop. Hence, the experiment was conducted at Zonal Agricultural Research Station (ZARS), University of Agricultural Sciences (UAS), Gandhi Krishi Vigyana Kendra (GKVK), Bangalore, during kharif and rabi seasons of 2022 and 2023 to evaluate modifications in source–sink relationship and assimilate partitioning for enhancing HI in sunflower. The experiment consisted of 9 treatments, tested in a randomized complete block design and replicated thrice using sunflower hybrid KBSH-44. The results revealed that among the different treatments, the application of 3000 ppm chlormequat chloride (cycocel) and double nitrogen (N) at sowing, combined with a micronutrient mixture at the ray floret stage, consistently outperformed others across seasons. These treatments notably increased plant height, leaf area index, crop growth rate, seed filling percentage and final seed yield. Defoliation treatments provided valuable insights into the plant’s ability to redistribute assimilates under reduced source conditions, demonstrating compensatory mechanisms within the crop. The study highlights the importance of integrating plant growth regulators (PGRs), precise nutrient management and strategic canopy modifications to enhance source-sink efficiency and overall productivity in sunflowers.